The Ethics of The Tripartite Tractate (NHC I, 5) : a A Study of Determinism and Early Christian Philosophy of Ethics - Linjamaa, Paul, (Nag Hammadi and Manichaean Studies ;, 2019)
In The Ethics of The Tripartite Tractate (NHC I, 5) Paul Linjamaa offers the first full length thematical monograph on the longest Valentinian text extant today. By investigating the ethics of The Tripartite Tractate , this study offers in-depth exploration of the text's ontology, epistemology, theory of will, and passions, as well as the anthropology and social setting of the text. Valentinians have often been associated with determinism, which has been presented as "Gnostic" and then not taken seriously, or been disregarded as an invention of ancient intra-Christian polemics. Linjamaa challenges this conception and presents insights into how early Christian determinism actually worked, and how it effectively sustained viable and functioning ethics.